Video Tutorial Kaligrafi Blackletter - Ainal Husna; Hendra Afriwan (DEKAVE : Jurnal Desain Komunikasi Visual, 2021)
The purpose of designing this BlackLetter Calligraphy video tutorial is to provide communicative and informative teaching to the target audience, namely Minang Typers as a community that houses letter artists. Video media was chosen in order  to  convey information  through  audio-visual  to  be  effective  because  it  can stimulate  two  senses  simultaneously  in  conveying  information,  namely  audio (hearing) and audio visual (sight).The method used in designing this video tutorial is a combination of the glass box and black box methods. The glass box and black box methods are inseparable methods because these two methods have their respective portion shapes to form balanced elements in creating or creating a work. The analytical approach uses 5W + 1H. This video tutorial creative design program goes through three stages, namely pre-production, production, and post-production. Keywords: Video, Calligraphy, Blacklette